Molecular Mechanisms Influencing Bacterial Conjugation in the Intestinal Microbiota - Neil, Kevin; Allard, Nancy; Rodrigue, Sébastien (Frontiers in Microbiology, 2021)
Bacterial conjugation is a widespread and particularly efficient strategy to horizontally disseminate genes in microbial populations. With a rich and dense population of microorganisms, the intestinal microbiota is often considered a fertile environment for conjugative transfer and a major reservoir of antibiotic resistance genes. In this mini-review, we summarize recent findings suggesting that few conjugative plasmid families present in Enterobacteriaceae transfer at high rates in the gut microbiota. We discuss the importance of mating pair stabilization as well as additional factors influencing DNA transfer efficiency and conjugative host range in this environment. Finally, we examine the potential repurposing of bacterial conjugation for microbiome editing.